What Do Unions Do to Innovation? An Empirical Examination of the Canadian Private Sector - Walsworth, Scott (Relations industrielles / Industrial Relations, 2010)
This article uses Canadian national data to examine the union effect on product innovation, a firm outcome which is widely researched in the management literature but has been less prominent in Industrial Relations scholarship. Using a longitudinal sample from the employer survey of the Canadian Workplace and Employee Survey, the union effect on a firm’s ability to create or improve a product is examined. According to the commonly held view that unions impede firm performance, the results should point to a negative relationship between unions and product innovation. Interestingly, a strong negative effect is not observed. In fact a small statistically significant positive union effect is reported. This result is considered to be robust. Across various specifications the presence of a union and the intensity of the presence (firm union density) have significant and positive effects on a firm’s ability to innovate new products over a seven year period (1999-2005).The results of this study do not imply that the presence of a union is an important determinant of product innovation. The results are noteworthy because they do not identify a negative relationship between unions and a measure of firm performance: product innovation. In this regard, the results give weight to the observation that there is very little empirical support for the popular argument that unions impede firm performance.In Canada the demise of organized labour is often justified as a necessary adjustment to increasingly competitive markets. Indeed the signing of the 1993 NAFTA has put unions under greater scrutiny for their impact on Canada’s ability to compete internationally. That unions make firms less competitive is commonly accepted as a reasonable assessment. The results of this study and a review of the empirical literature on the union effect on other key firm outcomes such as productivity, labour costs, employment growth, sales and profitability, suggest that the popularly held negative assessment of unions is not based on a conclusive body of literature.